Meta-Analysis of Problem Based Learning Models Impact towards of Problem Solving Skills in Physics Learning - Ummah, Nur Siyaadatul; Nadzirin, Ayunin; Zahro, Fithriatiz; Prahani, Binar Kurnia; Siswanto, Joko; Mubarok, Husni; Yohannes, Abebayehu; Nugroho, Yuli Sutoto; Alfin, Jauharoti (International Journal of Emerging Research and Review, 2023)
Objective this study is to analyze problem based learning models effect towards skills of problem solving in learning Physics. Problem based learning in physics learning can trigger students to participate in the teaching and learning process actively. It can motivate students to increase interest in scientific problems that occur and simultaneously stimulate skills in solving scientific problems. Method used in this study is meta-analysis, namely by conducting a literature review of 15 scientific articles that several national and international journals have published regarding problem based learning models impact on skills of problem solving published from 2018 to 2022. Results of this research are a problem based learning model that has a significant impact on improving problem solving skills in learning Physics. So, problem based learning model able to be implemented in learning Physics to enhance problem solving skills. Novelty of this research is a type of scientific article that is used not only published by national journals but also published by international journals published from 2018 to 2022